Metode Pendidikan Rasulullah Muhammad SAW Terhadap Kaum Perempuan - Akhmad Syahid (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2017)
Rasulullah Muhammad SAW as the umbrella of the ummah, with intelligence and wisdom has given an extraordinary example, among the attention is to consider the figure of women as a figure who has a central role in a civilization ummah. With the educational methods that he has applied, he has produced generations of women as a generation of support for the advancement and spread of Islam throughout the country. Among the rights of women to be met is the right to get education, both general sciences education and the religious sciences, especially science about matters relating to issues of womanhood. Like the Fiqh woman, Fiqh raising children, Fiqh muamalah women who will sustain the main duties as a woman who will carry out the duties as a housewife. The method of education for women is exemplified by the Prophet Muhammad SAW is to provide time and place for women, and deliver material more specific besides other general materials with attention to aspects of intellectual and social background, and the process of education with a persuasive approach.